Analisis Karakteristik Soal Tes Literasi Matematika Unsur Aljabar Menggunakan IRT - Jasmine Nurul Izzah; Sintha Sih Dewanti (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2026)
Accurate measurement tools are needed to assess mathematical literacy in algebra. This study purposes to describe the test items characteristics in a mathematical literacy test using IRT. This study conducted by modifying the test development steps according to Downing & Haladyna. Subjects in this study were 179 7th students at a junior high school in Yogyakarta. The data collection instruments included a validation sheet and a test instrument. Data analysis techniques included content validity, construct validity, construct reliability, item and person characteristics using the PCM model. The results of the study indicate that there are eight items of mathematical literacy in algebra for seventh grade. All items are content-valid with a value of V >0.80, construct-valid (SLF > 0.45), and construct-reliable (CR>0.70). The difficulty level of items is in the good category with a b value in the range -2<b<2. The ICC curve shows that there are 2 items with ideal ICC and 6 items with non-ideal ICC. The information function and SEM indicate that the test instrument provides the best information when administered to students with abilities slightly below average. There were 6 questions that met the item fit criteria and 112 students who met the person fit criteria.